Anatomija človeškega telesa: Compendium topografske anatomije in navodila za vaje - Pejković, Božena (University of Maribor Press, 2021)
Anatomy of Human Body: Compendium of Topographic Anatomy and Instructions for Exercises. Compendium of topographic anatomy and instructions for exercises is a textbook manual that enables medical students together with lectures, seminaries, exercises and studies of supplementary professional literature to repeat their already achieved knowledge in topographic anatomy in a short time, it informs the students with general regulations and most common procedures of anatomical macrodissection. 1st reprint of first edition: 9. 8. 2021 2nd reprint of first edition: 24. 6. 2024